PROFIL URETRITIS GONOKOKUS DAN NON-GONOKOKUS PADA PRIA DI RSUP. PROF. DR. R.D. KANDOU MANADO PERIODE 2009 – 2011 - Silalahi, Yan David Parulian; Suling, Pieter L.; Kapantow, Marlyn G. (Universitas Sam Ratulangi, 2013)
Abstract: Urethritis, an inflammation of the urethra, is divided into gonococcal urethritis and non-gonococcal urethritis. It is a venereal disease transmitted through sexual contact resulting in a complaint of pain sensation during urination. This was a descriptive retrospective study. Data were obtained from the registration of sexually transmitted infections from the Department of Dermatology and Venereal Diseases Prof Dr. R.D. Kandou Hospital Manado. The results showed that from 2009 until 2011 there were 82 male patients with urethritis; 56 patients (68.5%) with gonococcal urethritis and 26 patients (31.5%) with non-gonococcal urethritis. The highest number of patients (51 patients, 62%) were at the ages of 25-44 years. The most frequent patient jobs were civil employes (38 patients, 46.4%), followed by students (10 patients, 12%), and jobless (8 patients, 10%). The most common sexual partners were female prostitutes (38 patients, 46.3%). The most frequent complaint of gonococcal and non-gonococcal urethritis patients was pain sensation during urination (35 patients, 42.7%). Conclusion: In this study, most male patients with gonococcal and non-gonococcal urethritis were at the ages of 25-44 years, worked as civil employees, and had sexual intercourse with female prostitutes. The most common complaint among them was pain sensation during urination Keywords: urethritis, gonococcal, non-gonococcal, males Abstrak : Uretritis adalah peradangan pada uretra dan terbagi menjadi uretritis gonokokus dan non gonokokus. Penyakit ini tergolong pada infeksi menular seksual (IMS) dengan penularan melalui hubungan seksual dan keluhan berupa nyeri saat berkemih. Penelitian ini bersifat deskriptif retrospektif; data diambil dari buku register infeksi menular seksual Bagian Ilmu Penyakit Kulit dan Kelamin RSU Prof Dr. R.D. Kandou Manado. Hasil penelitian memperlihatkan dari 82 kasus laki-laki dengan uretritis gonokokus (UG) non gonokokus (UNG) tahun 2009-2011 terdapat 56 pasien (68,5%) dengan UG dan 26 pasien (31,5%) dengan UNG. Usia 25-44 tahun merupakan kelompok usia terbanyak yaitu 51 pasien (62%). Jenis pekerjaan yang tersering untuk pasien UG dan UNG ialah pegawai sebanyak 38 orang (46,4%). Pasangan seksual pasien uretritis gonokokus dan non gonokokus yang tersering ditemukan ialah wanita pekerja seksual (WPS) sebanyak 38 orang (46,3%). Keluhan tersering pada pasien uretritis gonokokus dan non gonokokus ialah nyeri saat berkemih sebanyak 35 orang (42,7%). Simpulan: Dalam penelitian ini, pasien laki-laki dengan uretritis gonokokus dan non gonokokus tersering pada kelompok usia 25-44 tahun, jenis pekerjaan pegawai, dan pasangan seksual terbanyak wanita pekerja seksual. Keluhan yang tersering dikemukakan ialah nyeri saat berkemih. Kata kunci: uretritis, gonokokus, non-gonokokus, laki-laki